2013
DOI: 10.1093/jmcb/mjt025
|View full text |Cite
|
Sign up to set email alerts
|

ESCRT components regulate the expression of the ER/Golgi calcium pump gene PMR1 through the Rim101/Nrg1 pathway in budding yeast

Abstract: The endosomal sorting complex required for transport (ESCRT) complexes function to form multivesicular bodies for sorting of proteins destined for the yeast vacuole or the mammalian lysosome. ESCRT components are well conserved in eukaryotes, and their mutations cause neurodegenerative diseases and other cellular pathologies in humans. PMR1 is the orthologous gene of two human genes for calcium pumps secretory pathway Ca(2+)-ATPase (SPCA1, ATP2C1) and sarco/endoplasmic reticulum Ca(2+)-ATPase (SERCA, ATP2A2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 62 publications
5
43
0
Order By: Relevance
“…Subsequently, the intracellular Ca 2ϩ level is reduced to the basal level due to the uptake of Ca 2ϩ by organelles and the inhibition of Ca 2ϩ release from the vacuole. While this set of calcineurin targets generally seems to be coordinately regulated, the authors of another report (80) demonstrate that a deletion mutation of any of the components SNF7, SNF8, STP22, VPS20, VPS25, VPS28, and VPS36 of the endosomal sorting complex required for transport (ESCRT) complex activates Ca 2ϩ /CN signaling in yeast cells but, surprisingly, reduces the expression of the ER/Golgi calcium pump gene PMR1 by nearly half, independent of calcium stress. Although this finding seems to contradict the well-known fact that Ca2 ϩ /CN signaling positively regulates Pmr1, it is consistent with the important role of PMR1, together with PMC1, in preventing the lethal activation of calcineurin under standard (low-Ca 2ϩ ) conditions (81).…”
Section: Calcium-regulating Proteins In the Cytoplasmmentioning
confidence: 99%
“…Subsequently, the intracellular Ca 2ϩ level is reduced to the basal level due to the uptake of Ca 2ϩ by organelles and the inhibition of Ca 2ϩ release from the vacuole. While this set of calcineurin targets generally seems to be coordinately regulated, the authors of another report (80) demonstrate that a deletion mutation of any of the components SNF7, SNF8, STP22, VPS20, VPS25, VPS28, and VPS36 of the endosomal sorting complex required for transport (ESCRT) complex activates Ca 2ϩ /CN signaling in yeast cells but, surprisingly, reduces the expression of the ER/Golgi calcium pump gene PMR1 by nearly half, independent of calcium stress. Although this finding seems to contradict the well-known fact that Ca2 ϩ /CN signaling positively regulates Pmr1, it is consistent with the important role of PMR1, together with PMC1, in preventing the lethal activation of calcineurin under standard (low-Ca 2ϩ ) conditions (81).…”
Section: Calcium-regulating Proteins In the Cytoplasmmentioning
confidence: 99%
“…ESCRT components Snf7, Snf8, Stp22, Vps20, Vps25, Vps28 and Vps36 regulate the expression of the ER/Golgi calcium pump gene in yeast PMR1 , the ortholog of 2 human genes for calcium pumps—the secretory pathway Ca 2+ ‐ATPase (SPCA1, ATP2C1) and the sarco/ER Ca 2+ ‐ATPase (SERCA, ATP2A2) . It is reported that mutations in these ESCRT components can lead to almost 50% reduction in the expression of the ER/Golgi calcium pump gene PMR1 .…”
Section: Linking Escrt Pathway To Cell Death During Neurodegenerationmentioning
confidence: 99%
“…ESCRT components Snf7, Snf8, Stp22, Vps20, Vps25, Vps28 and Vps36 regulate the expression of the ER/Golgi calcium pump gene in yeast PMR1 , the ortholog of 2 human genes for calcium pumps—the secretory pathway Ca 2+ ‐ATPase (SPCA1, ATP2C1) and the sarco/ER Ca 2+ ‐ATPase (SERCA, ATP2A2) . It is reported that mutations in these ESCRT components can lead to almost 50% reduction in the expression of the ER/Golgi calcium pump gene PMR1 . Parallel evidences exist to highlight the importance of calcium pumps like the plasma membrane calcium ATPases (PMCAs) in the survival of spinal cord (SC) neurons; a reduction in PMCA2 expression induces death of SC neurons .…”
Section: Linking Escrt Pathway To Cell Death During Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Later studies showed its implication in processes such as sporulation and invasive growth, protection against Na + and Li + toxicity, cell wall assembly, protection against weak organic acids and regulation of calcium homeostasis 109110111112. A recent study 113 has extended the range of cell processes regulated by Rim101 to vacuolar functions.…”
Section: Signaling Pathways For Se Stressmentioning
confidence: 99%